ANTI-APOPTOTIC EFFECT OF CD95 RECEPTOR IN NA VE CD8+ T-LYMPHOCYTES IN CHILDREN WITH ACUTE INFECTIOUS MONONUCLEOSIS - E. N. Filatova (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
Acute infectious mononucleosis is a widespread viral disease, which most often manifests in childhood. The development of acute infectious mononucleosis is accompanied by the change of the CD4+/CD8+ T-lymphocytes ratio and the increase of the virus-specific CD8+ cytotoxic T-lymphocytes number. One of the T-lymphocytes number regulation mechanisms is the modulation of their progenitor cells apoptosis. The death receptor CD95 takes part in the regulation of T-lymphocytes apoptosis, including naïve T-cells. We studied the effect of CD95 receptor activation on apoptosis of naïve CD4+ and naïve cytotoxic CD8+ T-lymphocytes in healthy children and children with acute infectious mononucleosis. In this study children with acute infectious mononucleosis at the age of 9 to 16 years were included. For comparison healthy children of the same age with no clinical and laboratory signs of the disease were used. Naïve CD4+ and naïve cytotoxic CD8+ T-lymphocytes were isolated by negative magnetic immunoseparation. The analysis of naïve T-cells apoptosis and the CD95 receptor surface expression density was performed by using the flow cytometry analysis. The analysis of T-cells was performed in three variants: freshly isolated naïve CD4+ T-lymphocytes and naïve cytotoxic CD8+ T-lymphocytes, and also cells after 24 hours of the cultivation with anti-CD95 monoclonal antibodies or without them. In healthy children both CD95– and CD95+ naïve CD4+ T-lymphocytes underwent apoptosis. In children with acute infectious mononucleosis CD95– naïve CD4+ T-lymphocytes lost their susceptibility to apoptosis induction. In healthy children and children with acute infectious mononucleosis CD95– naïve cytotoxic CD8+ T-lymphocytes were resistant to apoptosis in contrast to CD95+ naïve CD4+ T-lymphocytes. In healthy children CD95 receptor did not induce apoptosis of isolated naïve CD4+ T-lymphocytes and naïve cytotoxic CD8+ T-lymphocytes. In children with acute infectious mononucleosis CD95 receptor was involved in inhibition of apoptosis of naïve cytotoxic CD8+ T-lymphocytes and did not effect on the level of apoptosis of naïve CD4+ T-lymphocytes. We suggest that CD95-dependent suppression of naïve cytotoxic CD8+ T-lymphocytes apoptosis is a protective mechanism for the maintenance of a sufficient number of cytotoxic T-lymphocytes in the blood for the realization of effective antiviral immune response.